2014
DOI: 10.1007/s11999-014-3647-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Use of a Powered Ankle-foot Prosthesis Restore Whole-body Angular Momentum During Walking at Different Speeds?

Abstract: Background Whole-body angular momentum (H) influences fall risk, is tightly regulated during walking, and is primarily controlled by muscle force generation. People with transtibial amputations using passive-elastic prostheses typically have greater H compared with nonamputees. Questions/purposes (1) Do people with unilateral transtibial amputations using passive-elastic prostheses have greater sagittal and frontal plane H ranges of motion during walking compared with nonamputees and compared with using powere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
(54 reference statements)
0
33
0
Order By: Relevance
“…Angular momentum has been investigated over a range of walking tasks such as steady-state walking (Herr and Popovic, 2008), walking at increasing speeds (Bennett et al, 2010), incline/decline walking (Silverman et al, 2012) and stair ascent/descent (Silverman et al, 2014). Angular momentum has also been analyzed during other movement tasks such as sit-to-stand (Reisman et al, 2002; Riley et al, 1997) and recovering from a trip (Pijnappels et al, 2004; Potocanac et al, 2014), and in different patient populations including elderly (Kaya et al, 1998; Pijnappels et al, 2005; Simoneau and Krebs, 2000), amputee (D’Andrea et al, 2014; Pickle et al, 2014; Sheehan et al, 2015; Silverman and Neptune, 2011) and post-stroke (Nott et al, 2014) subjects, and children with cerebral palsy (Bruijn et al, 2011). Collectively, these studies suggest that whole-body angular momentum is an important measure to quantify dynamic balance during human movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angular momentum has been investigated over a range of walking tasks such as steady-state walking (Herr and Popovic, 2008), walking at increasing speeds (Bennett et al, 2010), incline/decline walking (Silverman et al, 2012) and stair ascent/descent (Silverman et al, 2014). Angular momentum has also been analyzed during other movement tasks such as sit-to-stand (Reisman et al, 2002; Riley et al, 1997) and recovering from a trip (Pijnappels et al, 2004; Potocanac et al, 2014), and in different patient populations including elderly (Kaya et al, 1998; Pijnappels et al, 2005; Simoneau and Krebs, 2000), amputee (D’Andrea et al, 2014; Pickle et al, 2014; Sheehan et al, 2015; Silverman and Neptune, 2011) and post-stroke (Nott et al, 2014) subjects, and children with cerebral palsy (Bruijn et al, 2011). Collectively, these studies suggest that whole-body angular momentum is an important measure to quantify dynamic balance during human movement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous work has shown that the range of frontal plane angular momentum is greater, and therefore less tightly regulated, in lower-limb amputees compared to non-amputees (D’Andrea et al, 2014; Pickle et al, 2014; Sheehan et al, 2015; Silverman and Neptune, 2011), which may explain why they are more susceptible to falling (Miller et al, 2001). Thus, understanding how individual muscles contribute to the regulation of frontal plane whole-body angular momentum has the potential to provide additional insight into the diagnosis and treatment of balance disorders.…”
Section: Introductionmentioning
confidence: 99%
“…H is tightly regulated during level-ground walking [1], but this regulation is affected by different walking tasks, such as sloped walking [2], and by neuromotor or musculoskeletal impairments, such as leg amputation [3]–[6], stroke [7], [8], and vestibular balance impairment [9]. However, current analyses of dynamic balance using H often incorporate two common practices.…”
Section: Introductionmentioning
confidence: 99%
“…Amputated side peak anterior-posterior propulsive forces are consistently, significantly lower than able-bodied subjects and the intact side during walking at speeds ranging from 0.75–1.75m/s. (D’Andrea et al, 2014; Sanderson and Martin, 1997). Intact side peak anterior-posterior forces are not different from able-bodied subjects at speeds of 0.75, 1.50 or 1.75m/s (significantly higher than controls at 1.0 and 1.25m/s), however to our knowledge have never been investigated at walking speeds higher than 1.75m/s (D’Andrea et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(D’Andrea et al, 2014; Sanderson and Martin, 1997). Intact side peak anterior-posterior forces are not different from able-bodied subjects at speeds of 0.75, 1.50 or 1.75m/s (significantly higher than controls at 1.0 and 1.25m/s), however to our knowledge have never been investigated at walking speeds higher than 1.75m/s (D’Andrea et al, 2014). Furthermore, the walk-to-run gait transition has not previously been characterized in unilateral, transtibial amputees.…”
Section: Introductionmentioning
confidence: 99%